The analysis of circe, an LTR retrotransposon of Drosophila melanogaster, suggests that an insertion of non-LTR retrotransposons into LTR elements can create chimeric retroelements. - Losada, A.; Abad, J.P.; Agudo, M.; Villasante, A. (Molecular Biology and Evolution, 1999)
Circe is a transposable element recently identified in Drosophila melanogaster which appears to be mostly associated with the constitutive heterochromatin. This element shows the structural features of a long terminal repeat (LTR)-containing retrotransposon: It is flanked by 240-bp-long terminal repeats, and its two open reading frames encode putative proteins resembling the gag and pol polyproteins of retroviruses. However, Circe displays striking similarities of both LOA and Ulysses, a non-LTR element and an LTR element, respectively. The result of its phylogenetic and structural analysis has allowed us to propose a new mechanism for non-LTR retrotransposon evolution.